DAMPAK PERAYAAN EKARISTI ONLINE DALAM KEHIDUPAN IMAN KELUARGA PADA MASA PANDEMI DI LINGKUNGAN WIDOHARJO PAROKI SANTO YUSUF GEDANGAN - Jumiati Oktavia; Joko Prayitno; Andarweni Astuti (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2022)
The corona virus outbreak in almost all countries, this deadly infectious disease is a new problem for all mankind in the world. Christians normally perform the Sunday Eucharist in the church, now having to perform the Eucharist online at home. The issue that arises is how the Eucharist is performed online in the widojo ward of saint Joseph building, how the consciousness of the people in following the Eucharist online in the family, to what extent the Eucharist is online in the family's faith. The purpose of this study is to know the extent of the Eucharist's influence online in the lives of the family's faith, the extent of people's awareness in keeping with Eucharist celebrations online, and the positive effects of Eucharist celebrations online in the lives of the united faith. By using a descriptive quantitative approach. Data collection using an angket, and an interview, results from the Eucharist ward in the widojo church of saint Joseph geddon associated with a streamline celebration of the Eucharist online, gives 73% of the human awareness of following Eucharist online, to what extent the Eucharist online in the faith results in 78%.